Involvement of Dopamine D1/D5 and D2 Receptors in Context-Dependent Extinction Learning and Memory Reinstatement - André, Marion Agnès Emma; Manahan-Vaughan, Denise (Frontiers in Behavioral Neuroscience, 2016)
Dopamine contributes to the regulation of higher order information processing and executive control. It is important for memory consolidation processes, and for the adaptation of learned responses based on experience. In line with this, under aversive learning conditions, application of dopamine receptor antagonists prior to extinction result in enhanced memory reinstatement. Here, we investigated the contribution of the dopaminergic system to extinction and memory reinstatement (renewal) of an appetitive spatial learning task in rodents. Rats were trained for 3 days in a T-maze (context ‘A’) to associate a goal arm with a food reward, despite low reward probability (acquisition phase). On day 4, extinction learning (unrewarded) occurred, that was reinforced by a context change (‘B’). On day 5, re-exposure to the (unrewarded) ‘A’-context took place (renewal of context ‘A’, followed by extinction of context ‘A’). In control animals, significant extinction occurred on day 4, that was followed by an initial memory reinstatement (renewal) on day 5, that was, in turn, succeeded by extinction of renewal. Intracerebral treatment with a D1/D5-receptor antagonist prior to the extinction trials, elicited a potent enhancement of extinction in context ‘B’. By contrast, a D1/D5-agonist impaired renewal in context ’A’. Extinction in the ‘A’ context on day 5 was unaffected by the D1/D5-ligands. Treatment with a D2-receptor antagonist prior to extinction had no overall effect on extinction in context ‘B” or renewal in context ‘A’, although extinction of the renewal effect was impaired on day 5, compared to controls. Taken together, these data suggest that dopamine acting on the D1/D5-receptor modulates both acquisition and consolidation of context-dependent extinction. By contrast, the D2-receptor may contribute to context-independent aspects of this kind of extinction learning.